Adaptasi Mahasiswa Papua di Universitas Sumatera Utara dan Universitas Negeri Medan 2012-2021 - Lister Eva Simangunsong; Natalia Oagay (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2026)
This study examines the adaptation process of Papuan students studying at Universitas Sumatera Utara (USU) and Universitas Negeri Medan (Unimed) during 2012–2021. Differences in culture, language, social interaction, and learning systems often create adaptation challenges for students migrating from eastern Indonesia to Sumatera Utara. This research aims to describe the forms of adaptation undertaken by Papuan students and to identify supporting and inhibiting factors during their adjustment process. The study employed a qualitative descriptive-historical approach. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that Papuan students adapt academically, socially, culturally, and emotionally by building peer relationships, engaging in student organizations, maintaining cultural traditions, and receiving support from families and campus environments. Despite various challenges, Papuan students successfully developed dual identities by preserving their cultural roots while adopting local norms to support academic success.